The Role of Symbolic Modeling Technique in Group Guidance to Improve Students' Understanding of Sexual Education - Saputra, Randi; Maulita, Nadia; Fazny, Bella Yugi; Nurrahmi, Hesty; Fatin, Abdul (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2024)
Research Objectives:The purpose of this study was to increase the understanding of Islamic guidance and counseling students about the importance of sexual education as a preventive measure for sexual violence in the community through group guidance services using symbolic modeling techniques.Research Methods:This research uses the type of Guidance and Counseling Action Research (PTBK) conducted on 10 students of the Islamic Guidance and Counseling (BKI) study program. The data analysis processed is qualitative data analysis Miles, Huberman, and Saldana, namely condensing data, then presenting data, and drawing conclusions. In addition, researchers also used quantitative data analysis to obtain comparative data for cycle 1 and cycle 2. The analysis used a percentage formula by looking at the comparison of the results from cycle 1 and cycle 2 to see an increase in students' understanding of sexual education.Research Results:The lack of sexual education to students causes a lack of knowledge and awareness of cases of sexual violence that occur in the surrounding environment. Increased understanding of sexual education can be a preventive solution in reducing cases of sexual violence and creating a pioneer model for preventing sexual violence in the community.Conclusion:Increasing understanding of sexual education by providing group guidance services using symbolic modeling techniques that aim to prevent sexual violence also provides positive benefits for the development of student potential. So that Islamic guidance and counseling students can become good models and examples for the community.Implications:This article is expected to provide additional insight to guidance and counseling practitioners regarding group guidance services using symbolic modeling techniques in increasing understanding of sexual education in the community. This article is also expected to be a reference for socialization programs to prevent cases of sexual violence.